2011
DOI: 10.1016/j.scr.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of infarct size by intravenous injection of uncultured adipose derived stromal cells in a rat model is dependent on the time point of application

Abstract: Stem cell therapy is a promising tool to improve outcome after acute myocardial infarction (AMI), but needs to be optimized since results from clinical applications remain ambiguous. A potent source of stem cells is the stromal vascular fraction of adipose tissue (SVF), which contains high numbers of adipose derived stem cells (ASC). We hypothesized that: 1) intravenous injection can be used to apply stem cells to the heart. 2) Uncultured SVF cells are easier and safer when cultured ASCs. 3) Transplantation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 36 publications
2
57
0
Order By: Relevance
“…Consistent with previous findings [28,29], H&E and Picrosirius red/fast green staining revealed that the hearts of recipients of ADSCs had a smaller scar area compared with those that Fig. 4.…”
Section: Histological Analyses 4 Weeks Post-transplantationsupporting
confidence: 91%
“…Consistent with previous findings [28,29], H&E and Picrosirius red/fast green staining revealed that the hearts of recipients of ADSCs had a smaller scar area compared with those that Fig. 4.…”
Section: Histological Analyses 4 Weeks Post-transplantationsupporting
confidence: 91%
“…SVF cells, which are traditionally isolated through enzymatic processing, contain MSCs, endothelial (progenitor) cells, immune cells, smooth muscle cells, pericytes and other stromal components [18]. SVF treatment has been shown to provide therapeutic effects similar to those of ASC treatment in osteochondral defects and myocardial infarction [19, 20], and SVF cells have been demonstrated to have similar neuroprotective effects and greater immunomodulatory properties than ASCs in experimental chronic autoimmune encephalitis studies [21]. The regenerative capacity of SVF cells has been validated in various therapeutic models, such as fat grafting, multiple sclerosis, burn injury, diabetes, radiation, Crohn’s disease, cardiac disease and bone defect models [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Cell size is an important factor especially when cells are injected intravenously, since larger cells can lead to obstruction of the lung. 34 It has been indicated that cells with a smaller cell size have a higher differentiation capacity. 35 The inability of hADSC to become confluent when cultured in FBS containing DMEM high glucose medium might be due to higher ROS production and thus could promote cell death.…”
Section: Discussionmentioning
confidence: 99%